DIALOG YANG REPRESIF: STUDI KASUS TERHADAP DIALOG MUI DAN JAI DI KUNINGAN - Flavius Floris Andries (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
A dialogue among religions is the basic need in the multicultural life of Indonesia. Without any interfaith dialogue, conflicts and violence in the name of religion are difficult to be avoided. However, the process of dialogue is not an easy task to do. There is a basic need to find the proper methods of dialogue, because a mistake in finding the methods will complicate the process of dialogue, the dialogue can be meaningless and failed. This research demonstrates the failure of a dialogue because of a mistake in finding methods of dialogue, which prevents the dialogue reaching its ends. Based on a case study, this research analyses the aspects that can lead to the failure of a dialogue between Islam (MUI) and JAI in Kuningan. This research is important because the conflicts and violence occurred on the basis of different ideologies between Islam and JAI have not met any solutions despite the engagement of both parties in some dialogues. This research found that the failure in the dialogue between Islam (MUI) and JAI in Kuningan was because of the repressive factors of Islamic groups represented by MUI and the attitude of the government as biased mediator.